Development And Evaluation Of Bioadhesive, Thermosensitive, In Situ Gelling Formulation Of Metronidazole And Diclofenac Potassium For Treatment Of Periodontal Disease - Wadi, Nida Mohammed Ali (2019)
The target in treatment of periodontal disease is to eliminate the pathogens responsible for infection and decrease the tissue inflammation. Treatment using non-surgical scaling and root planning could leave behind microorganisms leading to re-colonization. Administration of anti-microbial and anti-inflammatory drugs orally, even at therapeutic doses in patients leads to some side effects. Local administration of drugs obviates the drawbacks of other routes of administration. The study was aimed to develop a syringeable, bioadhesive, sustained release, thermosensitive in situ gelling formulation of metronidazole and diclofenac potassium for the treatment of periodontal disease, which was delivered directly to the site of action. A simple HPLC-UV method that could simultaneously determine metronidazole and diclofenac potassium concentrations was developed and validated. The method was specific, precise and accurate. The two drug peaks were well resolved with good resolution. The sample run time was less than 12 min. The method was applied in drug assay, in vitro drug release study, in vitro drug permeation study and stability study of the gel formulations. Poloxamers 407 and 188 were used to prepare the in situ gelling formulations. Poloxamer of 30%w/w (poloxamer 407 and 188 at ratio of 2:1) showed gelation temperature close to the physiological temperature of the oral cavity. Xanthan gum and Carbopol 934 were incorporated to provide bioadhesive properties and sustain the drug release.